The syncope as a debut form of mitral stenosis - Vega-Candelario, Rodolfo (2020)
Introduction: The common mechanism to the syncope is a transient alteration in cerebral blood flux, this fact generate a temporary decrease in the brain metabolism with involvement of the ascending reticular system and cerebral cortex. The syncope due to mitral stenosis does not appear in the reviewed literature. Objectives: To show a clinical case from a patient with mitral stenosis that debuts with recurrent syncope. Clinical case: A 45-year-old patient, mestizo without history of disease, a farmer, is admitted to the internal medicine ward for recurrent syncope. He was evaluated by a neurologist and a cardiologist; he was diagnosed with critical mitral stenosis with severe pulmonary hypertension and a right ventricular Systo-diastolic dysfunction. After the mitral valve replacement by cardiovascular surgery, he did not suffer syncopal episodes again and leads a normal biopsychosocial and work life. Comments: The critical mitral stenosis causes decreased in the ventricular filling and decreased the cardiac output with decreased cerebral blood flux, accentuated by the severe pulmonary hypertension and the right heart failure. This fact caused repetitive syncope.